Effect of Different Concentrations of Amphiregulin/Neurgulin/ Tumour Necrocis Factor α on in vitro Maturation of Ovine Oocytes - Somashetty, Ramesh H.; Sumanta, Nandi; Venkatesh, Girish K. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The objective of the present study was to examine the effect of different concentrations of ovarian peptides Amphiregulin (AREG) or  Neuregulin-I (NRG-I) or Tumour necrosis factor (TNF-α) on in vitro maturation of ovine oocytes collected from different sizes of ovarian  follicles. Oocytes isolated from different ovarian follicles (large antral follicles (LAFs>4mm), medium antral follicles (MAFs
Keywords: Cumulus oocytes complexes; Maturation; Follicle; Ovine; LAFs; MAFs; SAFs